2020
DOI: 10.1021/acs.nanolett.0c03655
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Re-entrance of Superconductivity in Ta2PdS5 Nanostrips

Abstract: The motion of Abrikosov vortices is the dominant origin of dissipation in type II superconductors subjected to a magnetic field, which leads to a finite electrical resistance. It is generally believed that the increase in the magnetic field results in the aggravation of energy dissipation through the increase in vortex density. Here, we show a distinctive re-entrance of the dissipationless state in quasi-one-dimensional superconducting Ta2PdS5 nanostrips. Utilizing magnetotransport measurements, we unveil a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…3(a), the reentrant superconductivity phenomenon occurs, i.e., non-zero resistances below T c0 appear again at low temperatures, which has been reported in a large variety of superconductors. [44][45][46][47][48][49][50]55] We have found that the reentrant superconductivity can be obtained in the curved sample at small θ and low currents or at large θ and high currents, as shown in Figs. 3(a) and 6(a).…”
Section: The ρ(T) At High Currentsmentioning
confidence: 71%
“…3(a), the reentrant superconductivity phenomenon occurs, i.e., non-zero resistances below T c0 appear again at low temperatures, which has been reported in a large variety of superconductors. [44][45][46][47][48][49][50]55] We have found that the reentrant superconductivity can be obtained in the curved sample at small θ and low currents or at large θ and high currents, as shown in Figs. 3(a) and 6(a).…”
Section: The ρ(T) At High Currentsmentioning
confidence: 71%
“…As the sample appears to be granular in nature (Fig. S8 ), SFs might be the most plausible mechanism responsible for the observed reentrant states and the associated negative MR 37 , 46 , 47 . In this scenario, the Cooper pairs are localized in individual grains and the conduction is mainly led by the single particle conduction channel.…”
Section: Discussionmentioning
confidence: 99%